STRATEGI BERTAHAN HIDUP MASYARAKAT DESA RAP RAP - Fatimah, Nyayu (Jurnal Masyarakat dan Budaya, 2013)
The present study describes food security in Rap Rap Village, Tatapaan sub-District, South Minahasa District. This qualitative study use interview and observation. The results show that mapalus, a traditional value, has become a valuable asset in a social life. It has been embedded as culture in the Village of Rap Rap as the wealth basis in the society. Besides, mapalus implies a reciprocity principle, requiring the members of the society to help each other, either in good or bad time. This solidarity as an extended family has become a key and a driving force in the society. Keywords: poverty, food security, survival strategy